Marriage Dispensation on the Grounds of Engagement: A Study of the Decision of the Mahkamah Syariyyah Sigli City from the Perspective of Islamic Law and Child Protection Policy - Ramadhan, Zakiy; Khairani, Khairani; Adnan, Boihaqi bin (Department of Government Studies, Universitas Syiah Kuala, 2025)
This study analyzes the legal considerations used by judges in granting marriage dispensation based on engagement at the Mahkamah Syariyah (Sharia Court) of Kota Sigli during the period 20222024. Using a case approach and statutory approach within a normative juridical framework, the findings show that judges considered the existence of an engagement, the physical and mental readiness of the couple, and family support. The Islamic legal principle preventing harm takes precedence over attaining benefit served as the main basis for the ruling, aligning with the concept of maslahah (public interest) in Islamic family law. However, from the perspective of child protection policy, this practice still carries potential risks to children's rights, especially in terms of education and protection from early marriage. It is concluded that the dispensation was granted based on maslahah, but it needs to be balanced with stricter adherence to child protection principles.